Efektivitas Pemberian Pujian Spesifik dalam Meningkatkan Fokus Belajar Siswa Sekolah Dasar - Frisky faradisa; Ibnu Muthi (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
This study aims to analyze the effectiveness of giving specific praise in improving the learning focus of elementary school students. Learning focus is a crucial aspect in supporting students' academic success, especially at the elementary education level. This study uses a literature review method with a descriptive qualitative approach. Data were obtained through searching and analyzing relevant literature, including scientific journals, books, and previous research results. The analysis technique used was thematic analysis to identify patterns and synthesize the main findings. The results of the study showed that specific praise delivered appropriately, directly, and relevant to students' positive behavior proved to be more effective than general praise in increasing students' attention, concentration, and learning participation. Specific praise is also related to increased self-confidence and learning motivation. However, its effectiveness is influenced by factors such as student characteristics, teacher consistency, and learning context. This study concludes that specific praise is a simple but powerful strategy that can be applied by teachers to create a more positive and focused learning environment. This study also provides implications for learning practices and teacher training in implementing positive reinforcement effectively.